2022
DOI: 10.14742/ajet.7743
|View full text |Cite
|
Sign up to set email alerts
|

Preparing pre-service teachers for instructional innovation with ICT via co-design practice

Abstract: Information and communications technology (ICT) is rapidly changing how we teach and how we learn. ICT can not only act as a teaching and learning aid but also reshape the delivery of instruction and bring about changes in education. Research has largely examined the effects of teacher education programs on their knowledge, attitudes, and beliefs of technology integration and relatively little attention has been paid to their ability to use ICT to innovate instruction. This study examined how pre-teachers enga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
(45 reference statements)
0
4
0
Order By: Relevance
“…A systematic review of 98 studies on teacher well-being has identified work-related key factors that contribute to teacher well-being, including work-related individual factors, like feelings of competence or efficacy and work-related contextual factors, such as collegial support, support for autonomy and supportive work environment (Hascher & Waber, 2021). However, in the context of ICT-related research on teachers, there has been a predominant focus on examining the impact of ICT on instructional practices and student learning outcomes (Chen et al, 2022;Passey, 2021;Wu et al, 2021). Limited understanding exists regarding the complex interplay of individual and contextual factors concerning the multidimensional nature of teacher well-being in ICT-enhanced teaching, particularly within the online teaching context necessitated by the pandemic.…”
Section: Teacher Well-beingmentioning
confidence: 99%
See 2 more Smart Citations
“…A systematic review of 98 studies on teacher well-being has identified work-related key factors that contribute to teacher well-being, including work-related individual factors, like feelings of competence or efficacy and work-related contextual factors, such as collegial support, support for autonomy and supportive work environment (Hascher & Waber, 2021). However, in the context of ICT-related research on teachers, there has been a predominant focus on examining the impact of ICT on instructional practices and student learning outcomes (Chen et al, 2022;Passey, 2021;Wu et al, 2021). Limited understanding exists regarding the complex interplay of individual and contextual factors concerning the multidimensional nature of teacher well-being in ICT-enhanced teaching, particularly within the online teaching context necessitated by the pandemic.…”
Section: Teacher Well-beingmentioning
confidence: 99%
“…Additionally, teacher self-efficacy serves as a mediator in the relationships between work-related factors and teacher well-being (Bakker & Demerouti, 2017;Han et al, 2020). Although there is extensive knowledge on the impact of ICT on instructional practices and student learning outcomes (Chen et al, 2022;Passey, 2021;Wu et al, 2021), few studies have examined the intricate interplay of individual and contextual factors for university teachers' well-being in ICTenhanced teaching, particularly online teaching during the pandemic in non-Western contexts.…”
Section: Teaching Support In Ict-enhanced Teachingmentioning
confidence: 99%
See 1 more Smart Citation
“…In summary, the goal of enhancing pre-service teachers’ instructional innovation capabilities has been promoted and supported by both educational policies and researchers. This has brought new challenges and development opportunities to teacher education in normal colleges and universities, and the fostering of pre-service teachers’ instructional innovation capabilities has become a subject worthy of attention (Chen et al, 2022; Zhang, 2022).…”
Section: Introductionmentioning
confidence: 99%